Ubiquity, diversity and physiological characteristics of Geodermatophilaceae in Shapotou National Desert Ecological Reserve - Sun, Hong-Min; Zhang, Tao; Yu, Li-Yan; Sen, Keya; Zhang, Yu-Qin (Frontiers in Microbiology, 2015)
The goal of this study was to gain insight into the diversity of culturable actinobacteria in desert soil crusts and to determine the physiological characteristics of the predominant actinobacterial group in these crusts. Culture-dependent method was employed to obtain actinobacterial strains from desert soil samples collected from Shapotou National Desert Ecological Reserve located in Tengger Desert, China. A total of 376 actinobacterial strains were isolated and 16S rRNA gene sequences analysis indicated that these isolates belonged to 29 genera within 18 families, among which the members of the family Geodermatophilaceae were predominant. The combination of 16S rRNA gene information and the phenotypic data allowed these newly-isolated Geodermatophilaceae members to be classified into 33 “species clusters”, 11 of which represented hitherto unrecognized species. Fermentation broths from 19.7% of the isolated strains showed activity in at least one of the six screens for antibiotic activity. These isolates exhibited bio-diversity in enzymatic characteristics and carbon utilization profiles. The physiological characteristics of the isolates from different types of crusts or bare sand samples were specific to their respective micro-ecological environments. Our study revealed that members of the family Geodermatophilaceae were ubiquitous, abundant, and diverse in Shapotou National Desert Ecological Reserve, and these strains may represent a new major group of potential functional actinobacteria in desert soil.